SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN KELAPA SAWIT BERBASIS ANDROID - Surianti Surianti; Nur Ain Banyal (Jurnal Ilmiah Matrik, 2021)
The lack of farmers' knowledge about various palm oil palm plant diseases and how to prevent plant is not attacked by the disease even with the lack of knowledge has led to mistakes in dealing with diseases that attack the oil palm plantations. On the other hand, to meet experts who are experts in the field of agriculture plant oil palm is very difficult, it is necessary for the right technology to solve the problem of oil palm plantations. One way to overcome this problem by building a plant disease expert system palm, to facilitate the farmers know the oil palm plant diseases. There are various methods in an expert system, but here using certainty factor. This study resulted in an expert system that can be used as a means for diagnosing the disease of oil palm trees are diseased, in the application development using Android SDK android studio and used to run android emulator on a computer or pc